Printing fine solid lines in flexographic printing process - Yusof, Mohd Sallehuddin (2011)
Solid lines are essential to enable printing of conducting tracks for various electronic applications. In the flexographic printing process, the behaviour of the printing plate plays a vital role in how ink is printed onto the substrate as it deforms when passing through the printing nip. This deformation is dependent on the material properties of the plate, the geometry of the lines and the pressure within the printing nip. These will influence the printed track width and the ink film thickness, which will affect the electrical performance of the printed conductors. This thesis will focus on experiments on Flexographic printing capabilities in printing ultra fine solid lines. The development of a measurement technique which leads to successfully capturing the printing plate line geometry details through the application of interferometry techniques, will be demonstrated. This information is used in a Finite Element models to predict the deformation and consequent increase in line width using both a linear and non linear material models, the latter being based on a hyperelastic representation. A series of experiments on a bench top printer and a web press machine to determine the capabilities and the limitation of the Flexographic printing process in printing fine solid is also presented. Through the experiments conducted the link between the IGT-Fl printer and an industrial scale web press machine has been established where the success in study on certain printing parameters and its affects lead to a successful prints of 50ym line width with 50pm line gaps. The experiments also point the importance of light engagement pressures within the printing train and the requirements for using anilox cylinders having fine engraving. The work also shows than process parameters (eg, contact pressures) that are important for graphics printing have a similar effect when the processes is used to print fine line features . .